Effectiveness of Environmental Based Thematic Learning Tools (EBTLT) in Improving the Science Literacy Skills - Harisna, Rubita; Sutarto, Joko (Journal of Primary Education, 2020)
Environment-based learning is needed to increase student’s activity through environmental empowerment, which can solve the problems in society as well as to improve students’ scientific literacy. The objective of this research was to analyze the effectiveness of environment-based thematic learning on fourth grade by contextual approach in improving students' scientific literacy skills. This research is a quasi-experimental research by implemented Environmental-Based Thematic Learning Tools (EBTLT). The subject of this research is determined by purposive cluster. They were 25 students as control class, 33 students as the experiment class 1, and 27 students as the experiment class 2. The data analysis was used completeness test, N-Gain analysis, and independent sample t-test. The results showed that the first experimental class and second experimental class students achieve classical completeness > 75%, the value has increased after implemented EBTLT in high category. The average score of science literacy skills and student activity in both experimental class was higher than that of the control class. It can be concluded that students who received EBTLT more effective in improving science literacy skills than students who received basic learning and the activities can create character values for learners